(untitled) (Research, Society and Development, 2025)
This study aimed to evaluate noise pollution generated by fixed and mobile sources in the urban area of the Pichincha canton, Manabí province. In situ sound pressure measurements were taken in different urban areas, complemented with georeferencing and comparative analysis with current environmental regulations. In addition, vehicle dynamics were analyzed to understand their relationship with noise pollution. The records indicate that hospital and educational areas have average levels of 72 dB(A), exceeding the limit of 45 dB(A), which represents a risk to the population. In the commercial and mixed commercial areas, values ranged between 72 dB(A) and 76 dB(A), while the mixed residential area reached 66 dB(A), all above the regulatory limits. There was an increase in vehicular traffic on weekends, contributing significantly to ambient noise. The implementation of quiet zones in sensitive areas, traffic regulation, installation of noise barriers, and public awareness campaigns are recommended. These strategies would help reduce noise pollution and improve the quality of life of the inhabitants.